2017
DOI: 10.17583/ijep.2017.2357
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Validation of the MUSIC® Model of Academic Motivation Inventory: Evidence from Chinese- and Spanish-Speaking University Students

Abstract: The purpose of this study was to examine the extent to which Chinese and Spanish translations of the College Student version of the MUSIC ® Model of Academic Motivation Inventory (MUSIC Inventory; Jones, 2012) demonstrate acceptable psychometric properties. We surveyed 300 students at a university in China and 201 students at a university in Colombia using versions of the MUSIC Inventory that were translated into Chinese and Spanish, respectively. To assess the psychometric properties of the inventory, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 18 publications
(30 reference statements)
3
26
0
Order By: Relevance
“…Because we administered the MMI in the U.S., Canada, Denmark, and Japan, these results demonstrate that the Cognitive Training version of the MMI can be used in a variety of cultures and countries. These findings are consistent with research studies using the MMI with students in countries such as China (Jones et al, 2017a), Colombia (Jones et al, 2017a), Egypt (Mohamed, Soliman, & Jones, 2013), Iceland (Schram & Jones, 2016), and Spain (Mora, Anorbe-Diaz, Gonzalez-Marrero, Martin-Gutierrez, & Jones, 2017). Thus, this study contributes to a broader body of evidence demonstrating the potential to use the MUSIC model in many different cultures and contexts.…”
Section: Overall Findings and Future Researchsupporting
confidence: 86%
See 2 more Smart Citations
“…Because we administered the MMI in the U.S., Canada, Denmark, and Japan, these results demonstrate that the Cognitive Training version of the MMI can be used in a variety of cultures and countries. These findings are consistent with research studies using the MMI with students in countries such as China (Jones et al, 2017a), Colombia (Jones et al, 2017a), Egypt (Mohamed, Soliman, & Jones, 2013), Iceland (Schram & Jones, 2016), and Spain (Mora, Anorbe-Diaz, Gonzalez-Marrero, Martin-Gutierrez, & Jones, 2017). Thus, this study contributes to a broader body of evidence demonstrating the potential to use the MUSIC model in many different cultures and contexts.…”
Section: Overall Findings and Future Researchsupporting
confidence: 86%
“…The fit indices provide a means to assess the factorial construct validity of the MMI scales because the model has been shown to consist of five different constructs (Jones et al, 2017a;Jones & Skaggs, 2016). To further assess the construct validity of the scales, we computed the coefficients of determination (r 2 ) to examine the relationships between the MMI constructs.…”
Section: Analysis and Interpretation Of Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from several studies have confirmed that students' MUSIC perceptions are distinct in a variety of educational settings, including courses in professional schools (Jones, Byrnes, & Jones, 2019;Pace, Ham, Poole, & Wahaib, 2016), undergraduate courses (Chittum, Jones, & Carter, 2019;Jones & Wilkins, 2013), middle and high school classes (Chittum & Jones, 2017;Parkes, Jones, & Wilkins, 2017), elementary school classes (Jones & Sigmon, 2016), and clinical training settings (Hansen et al, 2019). Furthermore, these studies have been conducted in a variety of cultures and countries, including Canada, Denmark, and Japan (Hansen et al, 2019); China and Columbia (Jones, Li, & Cruz, 2017); Egypt (Mohamed, Soliman, & Jones, 2013); and Iceland (Schram & Jones, 2016). In sum, a body of evidence has accumulated to demonstrate that the five MUSIC model components represent five different perceptions that students can have in educational settings.…”
Section: Evidence For the Music Modelmentioning
confidence: 79%
“…Given that students' MUSIC perceptions can be distinct in an educational setting, some researchers have investigated the relationships between students' MUSIC perceptions and important outcomes, such as effort, instructor ratings, and course ratings. Evidence from studies with undergraduate students suggests that students' MUSIC perceptions are positively related to their effort, instructor ratings, and course ratings (Chittum et al, 2019;Jones, 2010;Jones & Skaggs, 2016;Jones et al, 2017). However, more studies are needed to examine whether these relationships also exist in other types and sizes of courses.…”
Section: Evidence For the Music Modelmentioning
confidence: 99%